Success, survival, and failure of dental implants placed in the augmented bone and pristine bone: a retrospective cohort study - Tao, Chih-Yun. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: Yumi Ogata, Yoon Kang, and Sarah Pagni.; Keyword: Dentistry.